PENGAWASAN KEIMIGRASIAN PROGRAM DESA BINAAN DALAM PERSPEKTIF GOOD GOVERNANCE BERBASIS TRI HITA KARANA - Made Kalpika Pradnyaswari; Ni Wayan Widhiasthini; I Nyoman Subanda; Ni Putu Bayu Widhi Antari (JURNAL ILMIAH EDUNOMIKA, 2025)
The increasing mobility of foreign nationals in Bali requires an immigration monitoring system that is adaptive, participatory, and rooted in local values. This study aims to analyze the implementation of the Immigration Fostered Village Program by the Class I Immigration Office of TPI Denpasar in Sayan Village, Ubud District, Gianyar Regency, and to identify its challenges and opportunities. The program was designed as a preventive measure against human trafficking (TPPO) and people smuggling (TPPM) through community-based monitoring. This research employs a descriptive qualitative method involving nine informants selected through purposive sampling. Data were collected through in-depth interviews, observation, and documentation studies, and analyzed using the Miles and Huberman model, consisting of data reduction, data presentation, and conclusion drawing. Data validity was tested using source and technique triangulation. The findings indicate that the program is still in its early stage, mainly limited to socialization activities without follow-up mentoring. The main obstacles include limited budgets, human resources, and public participation. Nonetheless, there are opportunities for improvement through cross-sectoral collaboration and digitalized communication. The study recommends applying the Tri Hita Karana values and good governance principles to achieve a collaborative and sustainable immigration governance system in Bali.